Enhanced production of alkaline protease by a mutant of Bacillus licheniformis N-2 for dehairing - Muhammad Nadeem; Javed Iqbal Qazi; Shahjahan Baig (Brazilian Archives of Biology and Technology, 2010)
The purpose of the present investigations was to improve the yield of alkaline protease for leather dehairing by subjecting the indigenous proteolytic strain Bacillus licheniformis N-2 to various mutagenic treatments viz. UV irradiations, NTG (N-methyl-N-nitro-N-nitrosoguinidine) and MMS (methyl methane sulfonate). After screening on skim milk agar plates, a total of nine positive mutants were selected for shake flask experiments. Among these, the best proteolytic mutant designated as UV-9 showed 1.4 fold higher alkaline protease activity in preoptimized growth medium than the parent strain. The fermentation profile and kinetic parameters such u(h-1), Yp/s, Yp/x, Yx/s, q s, Qs, q p and Qp also indicated the superiority of the selected mutant UV-9 for alkaline protease production over the parent strain and rest of the mutants. The dehairing capability of mutant UV-9 alkaline protease was analyzed by soaking goat skin pieces for different time intervals (3-15 h) at 40 º C. A complete dehairing without degradation of collagen was achieved after 12 h, indicating its commercial exploitation in leather industry.